2012
DOI: 10.1007/s00068-012-0230-x
|View full text |Cite
|
Sign up to set email alerts
|

Fascia iliaca compartment block reduces morphine requirement pre-operatively for patients with fractured neck of femur

Abstract: Fascia iliaca compartment block is a safe and effective method of providing analgesia to patients with fractured neck of femur and reduces morphine requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Another study showed that FICNB reduces the requirement of morphine by 41% compared to those patients who received systemic analgesia (P=0.018). [9] The difference might be due to only few patients who were given opioid analgesia at the postoperative period in our hospital.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another study showed that FICNB reduces the requirement of morphine by 41% compared to those patients who received systemic analgesia (P=0.018). [9] The difference might be due to only few patients who were given opioid analgesia at the postoperative period in our hospital.…”
Section: Discussionmentioning
confidence: 92%
“…The two pop techniques are appreciated blindly while passing the fascia lata and fascia iliaca. [7][8][9] The FICNB has proved to be an easy and safe technique. It is free from complications because of the major nerves and vessels are far from the site of needle insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Foss et al describe their operators as anaesthetists with 2 years experience, whilst Monzón et al (2007Monzón et al ( , 2010 describe the operator as a 'physician'. Leeper (2007), Høgh et al (2008), Elkhodair et al (2011) Lees et al (2014 and Hanna et al (2014) use a mixture of ED junior medical staff and middle grades who have received a variety of training or possessed differing amounts of previous experience. Obideyi et al (2008) describes a nurse led FICB service and this was the only paper referring to this in a hospital setting pre surgery.…”
Section: Resultsmentioning
confidence: 97%
“…Among those studies reviewed, those that utilised ultrasound guidance and sampled a large patient population demonstrated the most significant positive effects of regional blockade. There is also consistent evidence that the use of regional nerve blocks can reduce the consumption of opiates following hip fracture , and reduce the incidence of opiate side‐effects and overdose .…”
Section: Methodsmentioning
confidence: 89%
“…To facilitate the translation of evidence into practice, these issues need to be addressed with support from administrators, policy makers, clinicians and funders. Education and training is vital to ensure that knowledge, confidence and competency in best‐practice nerve block techniques remain high among emergency staff . Identifying local champions, trainers and auditors could be a useful way to initiate change and shift thinking from a universal reliance on opiates for the management of acute pain in the elderly .…”
Section: Discussionmentioning
confidence: 99%